Phytoestrogen consumption and risk for cognitive decline and dementia: With consideration of thyroid status and other possible mediators. Issue 160 (June 2016) - Soni, M.; White, L.R.; Kridawati, A.; Bandelow, S.; Hogervorst, E.
Highlights: Type of soy product and aglycone composition may affect cognitive outcome. Thyroid dysfunction, old age and equol deficiency are associated with negative cognitive outcomes. Cognitive tasks that recruit the prefrontal cortex may be most sensitive to phytoestrogens. Optimal phytoestrogen dosage and intake in diet are yet to be determined. Abstract: It is predicted that around 20% of the worlds population will be age 60 or above by 2050. Prevalence of cognitive decline and dementia is high in older adults and modifiable dietary factors may be able to reduce risk for these conditions. Phytoestrogens are bioactive plant chemicals found in soy, which have a similarity in structure to natural estradiol (the most abundant circulating estrogen). This structural likeness enables phytoestrogens to interact with estrogen receptors in the brain, potentially affecting cognition. However, findings in this domain are largely inconsistent, with approximately 50% of studies showing positive effects of phytoestrogens on cognition and the other half resulting in null/negative findings. This paper provides an updated review of the relationship between consumption of phytoestrogens and risk for cognitive decline and/or dementia. In particular, possible mediators were identified to explain discrepant findings and for consideration in future research. A case can be made for a link between phytoestrogen consumption, thyroid status and cognition in older age, although current findings in this area are very limited. Evidence suggests that inter-individual variants that can affect phytoestrogen bioavailability (and thus cognitive outcome) include age and ability to breakdown ingested phytoestrogens into their bioactive metabolites. Factors of the study design that must be taken into account are type of soy product, dosage, frequency of dietary intake and type of cognitive test used. Guidelines regarding optimal phytoestrogen dosage and frequency of intake are yet to be determined.